DNA adducts in human urinary bladder and other tissues. - Phillips, D H (1993)
Tobacco smoking is associated with an increased risk of cancer in a number of organs, including bladder and lung. Tobacco smoke contains at least 50 known chemical carcinogens that exert their biological effects through their covalent binding to cellular DNA. Examining human DNA for the presence of altered nucleotides is a means of monitoring exposure to genotoxic chemicals. DNA isolated from 73 human bladder biopsies has been analyzed by 32P-postlabeling for the presence of aromatic/hydrophobic adducts. Butanol extraction of DNA digests resulted in up to a 3-fold greater recovery of adducts than nuclease P1 digestion. Among 16 nonsmokers, adduct levels were in the range 3.2-20.8/10(8) nucleotides (mean 9.7). Eight ex-smokers had values in the range 2.6-12.3 (mean 7.1). Thirteen smokers had adduct levels between 1.3 and 26.7 adducts/10(8) nucleotides (mean 9.5, not different from nonsmokers). Six cigar smokers had higher levels of adducts (mean 12.1, range 7.3-15.0), but pipe smokers did not (five samples, mean 8.6, range 2.9-12.7). A further 8 samples from nonsmokers and 17 from smokers were examined in more detail. Although most of the DNA binding appears not to be smoking related, the levels of one adduct were found to be on average 2-fold higher in smokers (p < 0.005, one-tailed t test). Studies on tissues of the respiratory tract demonstrate a correlation between DNA adduct levels and exposure to tobacco smoke. Evidence to date on the influence of smoking on adducts in peripheral blood cells is equivocal; some studies demonstrate a significant effect, whereas others do not.(ABSTRACT TRUNCATED AT 250 WORDS)